1990
DOI: 10.1159/000293258
|View full text |Cite
|
Sign up to set email alerts
|

Different Antibody Response againstCandidaalbicansCell Wall Antigens in Cervicovaginal Secretions of Patients with Vulvovaginal Candidiasis

Abstract: Vaginal washings from 118 women were investigated by means of immunofluorescence for the presence of antibodies against Candidaalbicans. A significantly (p < 0.02) higher antibody titer was found in the samples from patients with clinically evident vulvovaginal candidiasis. Vaginal secretions from those patients with a positive culture for C. albicans were assayed by means of Western blotting. A distinct band pattern was found in the group of patients with a positive culture and the classical clinical picture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Differences between group I and the rest of the groups were mainly at the expense of IgG antibodies. This results is in agreement with our previous work [6], and it may be related to the Candida species isolated, since in both stud ies group I patients were predominantly infected by C. albicans serotype A. No correlation was found between local and systemic anti-C. albicans total immunoglobu lins, IgA, IgG and IgM antibodies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Differences between group I and the rest of the groups were mainly at the expense of IgG antibodies. This results is in agreement with our previous work [6], and it may be related to the Candida species isolated, since in both stud ies group I patients were predominantly infected by C. albicans serotype A. No correlation was found between local and systemic anti-C. albicans total immunoglobu lins, IgA, IgG and IgM antibodies.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, the possibility of a spontaneous in vivo transformation from asymptomatic colonization to symptomatic vaginitis through a selection of more viru lent clones capable of causing acute invasive disease has been suggested [5]. On the other hand, we have recently been able to demonstrate how the local immune response of the vaginal environment is qualitatively different in those patients who show the full clinical syndrome of Candida albicans vulvovaginitis, when compared to the asymptomatic carrier or uninfected counterparts [6].…”
Section: Introductionmentioning
confidence: 89%
“…Recurrent vaginal candidiasis occurs in ostensibly immunocompetent women who are not unusually susceptible to other infections, in the presence of established humoral and cell-mediated immune responses against the yeast. A comparison of antibody profiles from women with chronic recurrences and appropriate controls has not revealed any consistent differences in either serum (162) or vaginal secretions (142), although one study identified a unique band pattern in cervicovaginal secretions from culture-positive patients with a classical clinical presentation (306). Nevertheless, it seems probable that susceptibility in these women is associated with some form of T-lymphocyte defect.…”
Section: Chronic Vaginal Candidiasismentioning
confidence: 99%
“…Vaginal washes from 37 patients with vulvovaginal C. albicans infection were obtained by instillation and subsequent aspiration of 10 ml of sterile isotonic saline into the posterior vaginal fomix and they were processed as described previously [14]. Briefly, each wash was centrifuged at 400 9 for 10 min and the supernatants were concentrated 10 times by lyophilization.…”
Section: Antibodiesmentioning
confidence: 99%